Barriers and facilitators to evaluation of health policies and programs: Policymaker and researcher perspectives. (October 2016) - Huckel Schneider, Carmen; Milat, Andrew J.; Moore, Gabriel
Highlights: Evaluation of public programs faces ongoing challenges of researcher—policy collaboration. Political and system factors act as macro-level barriers to good evaluation. These barriers are manifested as time and funding constraints and contribute to fear of evaluation. Macro-level barriers feed into further micro and meso barriers. The dynamics of the policy maker-researcher relationship contributes to further challenges. Abstract: Our research sought to identify the barriers and facilitators experienced by policymakers and evaluation researchers in the critical early stages of establishing an evaluation of a policy or program. We sought to determine the immediate barriers experienced at the point of initiating or commissioning evaluations and how these relate to broader system factors previously identified in the literature. We undertook 17 semi-structured interviews with a purposive sample of senior policymakers (n = 9) and senior evaluation researchers (n = 8) in Australia. Six themes were consistently raised by participants: political influence, funding, timeframes, a 'culture of evaluation', caution over anticipated results, and skills of policy agency staff. Participants also reflected on the dynamics of policy-researcher relationships including different motivations, physical and conceptual separation of the policy and researcher worlds, intellectual property concerns, and trust. We found that political and system factors act as macro level barriers to good evaluation practice that are manifested as time and funding constraints and contribute to organisational cultures that can come to fear evaluation. These factors then fed into meso and micro level factors. The dynamics of policy-researcher relationship provide a further challenge to evaluating government policies and programs.